Investigation of crack propagation and acoustic emission characteristics in jointed rock under freeze–thaw cycles based on DEM - Yong Zhao; Qianbai Zhao; Tianhong Yang; Yanlong Chen; Penghai Zhang; Honglei Liu (International Journal of Mining Science and Technology)
In cold-region environments, where complex stresses and mining disturbances occur, rock masses are frequently segmented into discontinuous bodies by fractured structural planes, leading to anisotropic physical and mechanical properties. To explore the evolution of microcracks, degradation characteristics, and failure modes of fractured rocks in cold regions under the influence of freeze–thaw cycles, integrating laboratory experiments with the damage mechanics of freeze–thaw cycles. A numerical model for freeze–thaw cycle damage in rocks with various fracture dip angles was developed. The study revealed that the freeze–thaw expansion force generated during the pore water–ice phase transition is the primary driving factor behind freeze–thaw cycle damage. The initiation and propagation of microcracks and micropores, the detachment of matrix particles, and the loosening of clay mineral structures result in the transformation of the rock from a dense to a porous state, causing significant degradation in macroscopic mechanical properties. As freeze–thaw cycles increase, both the uniaxial compressive strength and the deformation modulus of the rock decrease significantly, with the failure mode gradually shifting from brittle instability to brittle-plastic or plastic failure. The findings of this study offer a practical approach to uncovering the mechanical response mechanisms between freeze–thaw damage in fractured rocks and structural planes.